Expression and function of the ectopic olfactory receptor OR10G7 in patients with atopic dermatitis - Tham, Elizabeth Huiwen; Dyjack, Nathan; Kim, Byung Eui; Rios, Cydney; Seibold, Max A.; Leung, Donald Y.M.; Goleva, Elena (Journal of allergy and clinical immunology, 2019)
Ectopic olfactory receptors (ORs) are found in the skin, but their expression and biological function in normal skin and skin form patients with atopic dermatitis (AD) are unknown. We sought to characterize the expression of ORs in the skin and assess OR-mediated biological responses of primary human keratinocytes in the presence of odorant ligands. OR expression was examined by using whole-transcriptome sequencing of skin tape strips collected from patients with AD and healthy control (HC) subjects. OR10G7 and filaggrin 1 (FLG-1) expression was analyzed by using RT-PCR and immunostaining in skin biopsy specimens and primary human keratinocytes from patients with AD and HC subjects. ATP and cyclic AMP production by control and OR10G7 small interfering RNA–transfected keratinocytes in response to odorant stimulation with acetophenone and eugenol was assessed. A total of 381 OR gene transcripts were detected in the skin samples, with the greatest OR expression detected in the skin tape strips corresponding to the upper granular layer of the skin. OR10G7 expression was significantly increased in skin biopsy specimens from patients with AD compared with those from HC subjects (P = .01) and inversely correlated with FLG-1 expression (P = .009). OR10G7 expression was greatest in undifferentiated keratinocytes from patients with AD and was downregulated with progressive differentiation. Primary human keratinocytes produced ATP, an essential neurotransmitter in sensory pathways, in response to acetophenone and eugenol, odorants previously identified as potential ligands for this receptor. This response was abolished in OR10G7 small interfering RNA–transfected keratinocytes. OR10G7 is expressed at significantly greater levels in undifferentiated keratinocytes from patients with AD compared with HC subjects. OR10G7 is likely involved in transmission of skin-induced chemosensory responses to odorant stimulation, which might modulate differential nociceptive responses in AD skin.